Treatment of Hepatic hydatidosis in Paysandú Situation diagnosis - Coiro, Miguel; Deleón, Gonzalo (Cirugía del Uruguay, 1999)
A retrospective study of 53 patients submitted to surgery due to hepatic hidatidosis with radical and conservative procedures is presented. The patronimic data is briefly analized as well as characteristic of the cysts, kind of technique employed and posoperatory course.